DESIGN AND SYMBOLIC CONSUMPTION - Pigulevskiy, Victor; Mirskaya, Liudmila (Revista Inclusiones, 2020)
This paper addresses the mechanism of symbolic consumption in modern culture as interaction of communicative and industrial design. Product design means creating a form of functionality that meets market requirements. Packaging, labeling and advertising immerse a produced object into the cultural context with imparts the associations with progress and the myths about commodity-based happiness to it. Brands are a semiotic system that connects the values of objects to market segments. A certain class of produced objects, machines and constructions receive the role of status markers for the owner who identifies himself through such object‐signs. Industrial and communicative design stimulates sales, stratifies and segments the consumer market. Marketing dictates the design objectives, and the emerging exchange value depends on the use value of objects and the saturation of the market with both low-end and high-end products.